Deformation and strengthening behavior of Al-Cu-based alloys at ambient and elevated temperatures - Mehran Shahhosseininia; Mohammadreza Zamani (Academia Materials Science)
Aluminum alloys typically exhibit low to intermediate strength. Heat treatment may improve their strength through precipitation hardening. Al-Cu-based alloys have shown appropriate mechanical properties based on their specific strengthening mechanisms. In this study, the as-cast Al-Cu (Mg-Ag-Ti-B) alloys were prepared at a medium cooling rate of 0.3 mm s−1. All specimens then underwent their specific solution heat treatment and artificial aging cycles. To evaluate the mechanical properties and deformation behavior of each alloy, the tensile test process was conducted at ambient and elevated (250°C) temperatures. For the Al-Cu-Mg-Ag class, the influence of grain size on yield strength (YS) and ultimate tensile strength (UTS) was studied. Fractography, the deformation behavior of each alloy was investigated at fracture surfaces using scanning electron microscopy (SEM). Results revealed that according to the precipitation hardening mechanism, the YS and UTS values were promoted after the heat-treatment procedure, while elongation-to-failure values were reduced compared with as-cast alloys. For elevated testing temperatures, the YS and UTS decreased or remained stable. The value of elongation to failure significantly increased compared to ambient temperature. The fine-grain size of the Al-Cu-Mg-Ag alloy indicated higher values of YS and UTS with a ductile behavior. SEM images illustrated that as-cast and heat-treated Al-Cu-Mg and Al-Cu-Mg-Ag alloys underwent a brittle deformation with intergranular-transgranular fracture mechanisms at ambient temperature. In contrast, at elevated testing temperatures, some dimples were observed to form. For as-cast and heat-treated Al-Cu and A205 alloys at ambient and elevated temperatures, small dimples with high depth were observed, confirming ductile deformation.